Tafsir Karya 'Â'isyah 'Abd Al-Rahmân Bint Al-Syâthi' (Suatu Rekonstruksi Metodologi Tafsir Kontemporer) - Mardan Mardan (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
Â’isyah ‘Abd. Al-Rahmân Bint al-Syâthi' (l.1913 M) was an Egyptian modern Moslem thinker. She was a professor in langustics and Arabic literature as well as quranic studies. One of her works is al-Tafsîr al-Bayâniy li al-Qur'ân al-Karîm”. This work was done as a response to the real condition of tafsir which merely focused on traditional interpretation. Bint al-Syati tried to interprete al-Quran with contextual and holisitic approach. This can be seen from the explanation of mufradat, tartîb, linguistics, as well as zawûq al-lugah. She then explained munasabat (relation) and the content of al-Quran. Shortly, method applied by Bint Syati is a modern interpretation.